(untitled) (Kairaranga, 2004)
This study investigated the caseload characteristics and the types of intervention implemented for children with autistic spectrum disorder (ASD). A survey was developed and distributed to 75 speech-language therapists working for Special Education within the New Zealand Ministry of Education. A total of 34 surveys were completed and returned. Analysis indicated that all the respondents were providing intervention for children with ASD. The majority of respondents had between one and five children with ASD on their caseload, of which, over half were aged under five-years-old. Visually based intervention methods. such as the Picture Exchange Communication System and social stories, were identified as the most frequently used and the respondents rated these interventions highly in terms of their perceived effectiveness for this population. The need for research to examine the efficacy of intervention approaches commonly used by speech-language therapists in working with children with AD is discussed.